Study of heart rate variability in healthy humans as a function of age: considerations on the contribution of the autonomic nervous system and the role of the sinoatrial node - Jorge Tasé, David A.; Garavaglia, Leopoldo; Defeo, Magdalena M.; Irurzun, Isabel M. (Frontiers in Medicine, 2025)
IntroductionThis study focused on the complex structure of heart rate variability (HRV) in the healthy heart. We studied the behavior of the heart rate variability (HRV) in healthy humans as a function of age from conception, including fetal data. We calculated statistical quantities such as the mean value of RR intervals (<RR>), the standard deviation of these intervals (SD), the power of the very low frequency (VLF), low frequency (LF) and high frequency (HF) bands, and the large-scale properties of HRV. We rationalized our findings discussing previous results that identify the signatures of the sinoatrial node (SAN) and the autonomic nervous system (ANS) in the HRV. This work provides further insights into the contribution of the SAN and the ANS to the cardiac rhythm in humans.MethodsWe analyzed a total of 205 HRV time series of healthy subjects. Of these time series, 195 correspond to born individuals aged between 1 month and 74 years, 50% females. The remaining ten time series correspond to healthy fetuses. The age was expressed in weeks, including gestational age to avoid finite size effects due to rounding errors. We included results previously reported in the literature.Results and discussion<RR> followed a power law with age from gestation and throughout life. The scale factor was 0.15 ± 0.01. SD evolved during pregnancy and underwent a sudden change at birth. From birth to puberty SD followed a scale behavior with age and a scale factor equal to 0.37 ± 0.04. The power spectrum density (PSD) was calculated as a function of age. We calculated the power of the VLF, LF, and HF bands. The HF/VLF ratio followed a power law with age, and the scale factor was −0.55 ± 0.06. The power spectrum was calculated, and we analyzed the effect of age on the scale behavior. Both the scale factor and the frequency range in which it was determined depended on age. scale behavior began at low frequencies and evolved from 1/f2-like behavior to 1/f-like behavior during pregnancy. After birth, 1/f behavior extended to occupy the entire frequency range in the puberty. With aging, the frequency range regressed again toward lower frequencies. The results demonstrated that the complex structure of HRV primarily reflects the structural complexity of the SAN, which continuously evolves from the fifth month of gestation and increases until reaching its peak at puberty. There is a white noise component in HRV that can be attributed to the ANS. Therefore, the SAN, structurally evolving from its appearance in the fifth month of gestation and throughout life, could be responsible for modulating the neuronal stimulation provided by the ANS.